BIMTEK PEMBUATAN PROMOSI SECARA ONLINE BAGI PEMILIK USAHA BERBASIS PERTANIAN DI KELURAHAN ANGGOEYA - Ima Astuty Wunawarsih; La Ode Arfan Dedu; Normal Bivariant Padangaran; Arfiani Arfiani (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2023)
This internal PKM activity will be intended to improve online marketing management for agricultural-based business owners in Anggoeya Village. The target to be achieved is the formation of online marketing for agriculture-based business owners. The output that will result from this internal PKM activity is the formation of a wider marketing network for the products of agricultural-based business owners, where business owners’ efforts to market their agricultural-based products can be widely spread in the area of Kendari City in particular and Southeast Sulawesi in general, making it easier for business owners to market their products. As a result, the majority of agricultural-based business owners in Anggoeya Village do not yet have online promotional media in the form of brochures, leaflets, or promotional CDs made using the Android mobile application in collaboration with universities (UHO), related governments, or product sales outlets. agriculture-based as a product marketing agent. The results of internal PKM activities can be published in national journals so that they can be used as examples for marketing agricultural-based products, contributions to science and technology development in the form of research results reports, and contributions for students involved in internal PKM activities to produce undergraduate theses. The method used to achieve the output goals and targets is an approach to marketing management through the creation of online promotional media for the products of agricultural-based business owners, whose products will be promoted to potential consumers of agricultural-based products.